(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
The seroprevalence of T. gondii infection in Mongolian sheep was investigated using an ELISA with rTgMAG1. A total of 175 serum samples collected from seven aimags in Mongolia were examined by an ELISA, and the results were compared with those from the commercialized LAT. Although, both tests showed high concordance, the ELISA detected 24% of infection and it seems to be more sensitive than the LAT detected 16.5% of infection in ovine samples. These results emphasize the usefulness of rTgMAG1 for diagnostic use in detection of T. gondii infection. Mongolian Journal of Agricultural Sciences Vol.15(2) 2015; 33-37